Highly Concentrated Autologous Platelet-Rich Plasma Restores Foveal Anatomy in Lamellar Macular Hole Surgery - Hagenau, Felix; Nobl, Matthias; Vogt, Denise; Schworm, Benedikt; Siedlecki, Jakob; Kreutzer, Thomas; Luft, Nikolaus; Priglinger, Siegfried (Klinische Monatsblätter für Augenheilkunde, 2021)
Background Lamellar macular holes (LMHs) are an entity of a progressive disease in which the efficacy of the therapy of choice, vitrectomy, seems to be reduced. It is unknown whether highly concentrated autologous platelet-rich plasma (PRP) is of value in the therapy of LMHs. The purpose of this study was to gauge the potential of highly concentrated PRP to restore foveal anatomy in LMH surgery.Patients and Methods In this interventional case series, eight eyes of eight patients with progressive LMH were included. All patients underwent a 23-gauge pars plana vitrectomy with induction of a posterior vitreous detachment and peeling of tractive epiretinal membranes whenever present. Under air tamponade, 0.1 mL of highly concentrated autologous PRP was applied. Subsequently, a gas or air tamponade was performed. All patients were instructed to rest in the supine position for the first 1 to 2 postoperative hours. Best-corrected visual acuity (BCVA) testing, microperimetry, spectral-domain optical coherence tomography (SD-OCT) and fundus photography were performed prior to and 3 months after surgery.Results SD-OCT showed closure of the macular defect with restoration of a normal foveal configuration in all (8 of 8) patients 3 months postoperatively. BCVA improved significantly, from 0.28 ± 0.08 to 0.12 ± 0.14 logMAR (Wilcoxon: p = 0.03). Microperimetry remained unchanged (24.13 ± 1.96 vs. 23.7 ± 1.54 dB; p = 0.46). No clinically significant intra- or postoperative complications were observed.Conclusion The use of highly concentrated PRP enables excellent anatomical and functional outcomes in the surgical therapy of LMH. Further prospective comparative trials are warranted to compare this promising technique with existing surgical strategies.
Keywords: lamellar macular hole; platelet-rich plasma; vitrectomy; peeling; retina